Macrophage‐derived osteopontin induces reactive astrocyte polarization and promotes re‐establishment of the blood brain barrier after ischemic stroke. Issue 12 (7th July 2015) - Gliem, Michael; Krammes, Kristina; Liaw, Lucy; van Rooijen, Nico; Hartung, Hans‐Peter; Jander, Sebastian
<x xml:space="preserve">Abstract</x> Infarcted regions of the brain after stroke are segregated from the intact brain by scar tissue comprising both fibrous and glial components. The extent and quality of scarring is influenced by inflammation. The matricellular glycoprotein osteopontin (OPN) is strongly induced in myeloid cells after stroke and may contribute to repair of ischemic brain lesions. To elucidate the role of OPN in scar formation, we induced photothrombotic brain infarction, characterized by circumscribed cortical infarctions with a well‐defined border zone toward the intact brain parenchyma. The cellular source and functional role of OPN was addressed by studies in OPN null (OPN‐/‐) mice, wild‐type mice depleted of hematogenous monocytes/macrophages by clodronate‐filled liposome treatment, and CCR2‐/‐ bone marrow chimeric mice characterized by impaired hematogenous macrophage influx into the infarctions. OPN was mainly produced by hematogenous macrophages infiltrating into the inner border zone of the infarcts whereas astrocyte activation occurred in the outer border zone. In OPN‐/‐ as well as macrophage‐depleted mice, reactive astrocytes failed to properly extend processes from the periphery toward the center of the infarctions. This was associated with incomplete coverage of neovessels by astrocytic endfeet and persistent leakiness of the damaged blood brain barrier. In conclusion, OPN produced by hematogenous macrophages induces astrocyte process extension toward the infarct border zone, which may contribute to repair of the ischemic neurovascular unit. GLIA 2015;63:2198–2207